The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/jcc.20377
|View full text |Cite
|
Sign up to set email alerts
|

Acetalization and thioacetalization of cabonyl compounds: A case study based on global and local electrophilicity descriptors

Abstract: Acetalization of benzaldehyde and substituted benzaldehydes (containing both electron-donating and electron-withdrawing groups) is explained qualitatively on the basis of global electrophilicity descriptor, w, as proposed by Parr and coworkers. The generated values of w can explain qualitatively the preferential electrophilic addition, and hence, the yield of acetalization obtained in an earlier experimental study carried by Patel and coworkers. The present study also reveals that although both steric and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…It is worth mentioning here that local descriptors from the grand canonical ensemble should be able to predict intra- and intermolecular reactivity because they generally possess a combination of a local and a global part [e.g., local softness: s ( r̅ ) = f ( r̅ ) S and philicity ω α ( r̅ ) = ωf α ( r̅ ) = (μ 2 /2η) f α ( r̅ ) = μ 2 Sf α ( r̅ )]. But the “intensive” nature of the Fukui function f ( r̅ ) has made these two descriptors “intensive” (in spite of the fact that the number of electrons and energies associated with evaluating them for intermolecular comparison are extensive) and so constrained the applicability of these two indices as intermolecular reactivity descriptors. Also, the global softness part in these two descriptors is “extensive”, but true (unambiguously) for a conductor.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning here that local descriptors from the grand canonical ensemble should be able to predict intra- and intermolecular reactivity because they generally possess a combination of a local and a global part [e.g., local softness: s ( r̅ ) = f ( r̅ ) S and philicity ω α ( r̅ ) = ωf α ( r̅ ) = (μ 2 /2η) f α ( r̅ ) = μ 2 Sf α ( r̅ )]. But the “intensive” nature of the Fukui function f ( r̅ ) has made these two descriptors “intensive” (in spite of the fact that the number of electrons and energies associated with evaluating them for intermolecular comparison are extensive) and so constrained the applicability of these two indices as intermolecular reactivity descriptors. Also, the global softness part in these two descriptors is “extensive”, but true (unambiguously) for a conductor.…”
Section: Introductionmentioning
confidence: 99%
“…The 'thermodynamic' aspect helps to explain, qualitatively, favourable product formation. 32,33 This aspect of w is established from the condition of maximal flow of electrons, i.e., when…”
Section: Introductionmentioning
confidence: 99%
“…However, w( r) will not provide any extra information than that by s( r) or f( r) as far as intramolecular reactivity is concerned. 259 Even though, individually this descriptor is 'extensive' (i.e., does not go to zero in the thermodynamic limit) in nature, here also 'intensive' nature of f( r) or f(k) makes philicity [w( r) or w(k)] indices applicable to limited cases 160,259,261,262,311,312 of intermolecular reactivities.…”
Section: Regioselectivity Of Large System In the Context Of Conceptua...mentioning
confidence: 99%
“…It was argued that the claim [i.e., global trend of electrophilicity (or nucleophilicity) originates from the local behavior of the molecules, or precisely of that atomic site which is most prone to electrophilic (or nucleophilic) attack] is logical for systems having only one distinctly strong site (electrophilic or nucleophilic) but does not hold true for systems having more than one site of comparable strength. For the justification of this argument, a thorough study was carried out by Roy et al,261,262 using numerical demonstrations and analytical reasoning. Finally, it was concluded that reliable intermolecular reactivity trend can be generated by global electrophilicity (or may be local hardness) and that is possible with local electrophilicity only for the systems having one distinctly strong site.…”
mentioning
confidence: 99%